Gender, Sexuality, Heteronormativity: reports of young people in the school context through vlogs (Research, Society and Development, 2020)
The present work approaches a subject that has not been clearly discussed by the schools and teachers: the questions of gender and sexuality. Our objective was to explore elements related to the young people in vlogs, keeping in mind to analyze the experience of gender and sexuality in a school environment. We intended to investigate the effects of the non-existence of this kind of policy in the school context, through analysis of vlogs. The research was of the qualitative nature, through the study exploratory character, and documental research utilizing vlogs of the internet. The results suggest that the internet is used as a support network, and the themes discussed by the young ones can be grouped in three axes: pedagogical control, deconstruction of heteronormativity culture and expression of fragilities.